Assessment: Cornerstone in Wound Management - Lozano-Platonoff, Adriana; Florida Mejía-Mendoza, Melissa Desireé; Ibáñez-Doria, Mónica; Contreras-Ruiz, José (My University, 2015)
Accurate and detailed assessment of wounds is an essential tool to plan proper management.1-4 It helps us define the state of the wound and the cause, and identify reasons for delayed healing.5,6 Initial assessment provides baseline data on the status of the wound and information to identify short-and long-term goals and determine appropriate interventions at each stage.4,7 Subsequent assessments provide us with valuable information on the progress of healing, help set objective measurements to check for at every visit, and provide uniformity in documentation.8 Proper assessment of the patient should include a wellperformed medical history, a general physical exam, and full assessment of the wound itself. ©Journal of the American College of Surgeons